2006
DOI: 10.1080/00498250600780191
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the recently encountered designer drug, methylone, in humans and rats

Abstract: The urinary metabolites of methylone in humans and rats were investigated by analysing urine specimens from its abuser and after administrating to rats with gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-electrospray ionization mass spectrometry (LC-ESI MS), using authentic standards. The time-course excretion profiles of methylone and its three metabolites in rats were further investigated after a single intraperitoneal dosing of 5 mg kg-1 methylone hydrochloride. Two major metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 15 publications
7
76
0
1
Order By: Relevance
“…Methylone increases the concentration of monoamine neurotransmitters such as serotonin, dopamine and noradrenaline in the human synaptic cleft, through inhibition of plasma membrane monoamine reuptake transporters [3]. Methylone acts as a stimulant of the central nervous system and has some hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylone increases the concentration of monoamine neurotransmitters such as serotonin, dopamine and noradrenaline in the human synaptic cleft, through inhibition of plasma membrane monoamine reuptake transporters [3]. Methylone acts as a stimulant of the central nervous system and has some hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Methylone is marketed on the internet as a high-purity plant food, which can give false confidence to teenagers and young adults attracted to stimulants similar to ecstasy (Figs. 1, 2, 3) [3].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, all published papers on pharmacokinetics of methylone are of a forensic nature (urinary collected specimens) (Crawse et al, 2012, Kamata et al, 2006 or from in vitro experiments (Mueller and Rentsch, 2012). This study constitutes the first approach to the kinetics of methylone based on in vivo blood sample data from laboratory animals and will be helpful to…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
“…Some reports describe that in humans the onset of effect of methylone appears at 15-30 min with a 2-3.5 h duration, but 6-24 h to return to "normal" status. Kamata et al (2006) identified the characteristic human and rat urinary metabolites of methylone that were of great importance in forensic analysis (Zaitsu et al, 2009). Moreover, some human sudden deaths related to methylone intake have been reported (Cawrse et al, 2012, Pearson et al, 2012 and some reported cases met the Hunter criteria for serotonin syndrome (Boyer andShannon, 2005, Warrick et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Kamata et al (2006) first evaluated methylone metabolism by determining parent and metabolite concentrations in urine from rats and humans exposed to methylone. These investigators showed that methylone is metabolized in a manner akin to MDMA involving two major pathways ( Figure 1): (1) O-demethylenation to form ( ± )-3,4-dihydroxy-N-methylcathinone (HHMC) followed by O-methylation to form ( ± )-4-hydroxy-3-methoxy-N-methylcathinone (HMMC) and (2) N-demethylation to produce ( ± )-3,4-methylenedioxycathinone (MDC) (Kamata et al, 2006). Methylone is primarily biotransformed by cytochrome p450 2D6 (CYP2D6) in humans, the same isoform responsible for metabolism of MDMA (Pedersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%